2020
DOI: 10.2147/jmdh.s281524
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Use of Facemasks During the COVID-19 Pandemic by the Brazilian Population</p>

Abstract: Objective: To evaluate the use of facemasks by the Brazilian population during the COVID-19 pandemic. Materials and Methods: This cross-sectional study involved 1277 participants who answered a web-based open survey with questions about the use of facemasks during the COVID-19 pandemic. Descriptive statistics with percentages was performed, and the responses were analyzed with chi-square and independent t-tests. Results: A total of 1277 answered the questionnaire, and most participants were female (81.8%). Alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
3
25
0
1
Order By: Relevance
“…To our knowledge, this study is the first to describe facemask usage and related problems in people with a chronic disease during the COVID-19 pandemic. Few studies have reported on facemask usage in the general population, and they included only local populations making them unsuitable for direct comparison with our study [11, 28]. In a US survey of 1056 adults conducted in May 2020, 825 (79%) reported to wear a mask.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study is the first to describe facemask usage and related problems in people with a chronic disease during the COVID-19 pandemic. Few studies have reported on facemask usage in the general population, and they included only local populations making them unsuitable for direct comparison with our study [11, 28]. In a US survey of 1056 adults conducted in May 2020, 825 (79%) reported to wear a mask.…”
Section: Discussionmentioning
confidence: 99%
“…Facemasks are especially important for people who are at high risk of severe COVID-19, such as elderly people or those with chronic diseases [8-10]. However, many people have reported discomfort resulting from the use of facemasks such as difficulty breathing, pain around the ears, headaches, or skin problems [11, 12]. High-risk populations such as people with a chronic respiratory disease may experience additional problems because of respiratory symptoms such as chronic cough and rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…Here, most respondents (67.3%) reported that the use of masks bothers them in some way (feel trapped, suffocated, feel shortness of breath, feel discomfort in the ears due to the elastics, fogs up the glasses). 14 Overall, even though people reported discontent over the mandatory use of masks, the general population followed the rule relatively well, as wearing masks signals empathy and prosocial behaviour toward members of the risk group. 15 Parallel to the easing of the measures, social activities, such as visiting friends also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on nonsurgical face masks have focused mainly on how to make face masks and people's attitudes toward face mask. [17][18][19] Researchers in Kenya proposed a proof of concept of a low-cost and reusable printed 3-D face mask for developing economies. Many countries, such as the US and Japan, have encouraged residents to make cloth face masks and release teaching videos on the CDC website.…”
Section: Discussionmentioning
confidence: 99%